2017
DOI: 10.1111/risa.12779
|View full text |Cite
|
Sign up to set email alerts
|

Sizing Up a Superstorm: Exploring the Role of Recalled Experience and Attribution of Responsibility in Judgments of Future Hurricane Risk

Abstract: Research suggests that hurricane-related risk perception is a critical predictor of behavioral response, such as evacuation. Less is known, however, about the precursors of these subjective risk judgments, especially when time has elapsed from a focal event. Drawing broadly from the risk communication, social psychology, and natural hazards literature, and specifically from concepts adapted from the risk information seeking and processing model and the protective action decision model, we examine how individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 78 publications
0
20
0
2
Order By: Relevance
“…Other behavioral outcomes that factored frequently in risk communication research were audience's willingness to take protective actions and seek risk information. Among prominent theoretical frameworks, the Protective Action Decision Model (Lindell & Perry, 2012), originally posited to predict behavioral intentions in the face of "natural" disasters, such as hurricanes (Rickard et al, 2017b), wildfires (McCaffrey, Wilson, & Konar, 2018), and tornadoes (Miran, Ling, Gerard, & Rothfusz, 2019), was also used to examine infectious diseases (Johnson, 2019) and chemical spills (Heath, Lee, Palenchar, & Lemon, 2018). Efforts to understand information seeking behaviors frequently built on the Risk Information Seeking and Processing model (Yang, Aloe, & Feeley, 2014), which integrates messenger, message, and audience characteristics to predict information seeking behaviors.…”
Section: Audiencesmentioning
confidence: 99%
“…Other behavioral outcomes that factored frequently in risk communication research were audience's willingness to take protective actions and seek risk information. Among prominent theoretical frameworks, the Protective Action Decision Model (Lindell & Perry, 2012), originally posited to predict behavioral intentions in the face of "natural" disasters, such as hurricanes (Rickard et al, 2017b), wildfires (McCaffrey, Wilson, & Konar, 2018), and tornadoes (Miran, Ling, Gerard, & Rothfusz, 2019), was also used to examine infectious diseases (Johnson, 2019) and chemical spills (Heath, Lee, Palenchar, & Lemon, 2018). Efforts to understand information seeking behaviors frequently built on the Risk Information Seeking and Processing model (Yang, Aloe, & Feeley, 2014), which integrates messenger, message, and audience characteristics to predict information seeking behaviors.…”
Section: Audiencesmentioning
confidence: 99%
“…People's risk perceptionrelated tweets include assessments of their exposure to harm based on where they live geographically (i.e., proximity to the ocean), vertically (i.e., what floor they live on), and structurally (i.e., what kind of building they reside in). Two common ways of parsing and measuring people's hurricane risk perceptions are as exposure and severity (Lazo et al 2015;Morss et al 2016Morss et al , 2018Rickard et al 2017), but these three aspects of perceived exposure revealed by our analysis indicate the nuanced ways that people think about their risk.…”
Section: July 2018mentioning
confidence: 85%
“…Although RPA and ISE are seemingly related, previous studies have focused mainly on relationships between risk perception and need for information-seeking (Huurne and Gutteling 2008;Terpstra et al 2014;Cahyanto et al 2016) instead of actual information-seeking ability. Little research has examined their theoretical relationship within the context of response to disasters, especially in the areas prone to frequent flooding (Zhu et al 2011;Richard et al 2017;Schumann et al 2018). Therefore, we examined the relationship between the two theoretical constructs and, to some extent, their reciprocal predictability.…”
Section: Limitationsmentioning
confidence: 99%